HUKUM PENGGUNAAN SOCIAL MEDIA OLEH WANITA YANG DALAM MASA ˜IDDAH - Izzatul Muchidah (State Islamic University (UIN) of Sunan Ampel, 2013)
This is a field research on the use of social media of women in the waiting period (case study in Gunung Anyar, Surabaya) in the perspective of Islamic law. This study aims to determine how the use of social media by women in the waiting period in Gunung Anyar-Surabaya is and whether it is in accordance with the provision of Islamic law. The technique of collecting data in this study is a direct interview from women who are in the waiting period using social media. The collected data are then analyzed by descriptive-deductive method. This study concludes that based on the provision of Islamic law, the use of social media by women in the raj’i waiting period in Gunung Anyar-Surabaya as a mean to entertain is legally permitted, moreover it has become one of the means of supporting their everyday business. However, if it is used to begin a new relationship with the opposite sex in order not to be known by public and moreover it can affect khitbah, this is not certainly in line with the provision of Islamic law since the raj’i divorced woman is still bounded within the marital contract with her husband. It is better for woman in the raj’i waiting period to have a feasible understanding related to both of the waiting period and its wisdom. Â Kata Kunci: hikmah, â€˜iddah, Â rajâ€™i dan social media.Â